(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
There is an acute shortage of Telfairia seeds during growing season, due to seed recalcitrance and the alternative uses to which the seeds are put. An experiment was conducted to determine the extent to which the seed of Telfairia occidentalis can be sectioned for the regeneration of propagules and to assess the growth response of the sectioned seeds. Pre-germinated seeds were sectioned into minisetts up to 32 per seeds. These were nursed for three (3) weeks and transplanted to the field in randomized complete block design with 3 replications. Whole seeds and seeds sectioned into two had the highest seedling emergence and reached their peaks at the end of 2 weeks after sowing. The least value of 30% seedling emergence was produced by seeds sectioned into 32. The vine growths of the whole seed (141 cm) and those sectioned into two (107 cm) were consistently and significantly higher than those of smaller seed sections that ranged from 16 - 84 cm. The relatively higher vigor expressed by whole seed over the sectioned seeds is probably due to the relatively higher food reserve in the former. The result obtained in this experiment has shown that it is possible to regenerate Telfairia occidentalis propagules by the use of seed sectioned up to 16. It is recommended that future studies should address the need to upgrade the seedlings emergence of sectioned seeds to achieve 100% survival in the nursery, and excellent plant stand in the field.